Factors influencing the online cosmetics purchasing behavior of students at Ho Chi Minh City University of Industry and Trade - Kha, Nguyen Van; Anh, Bui Pham Loan (International Journal of Innovative Research and Scientific Studies, 2025)
This study aims to identify and analyze the factors influencing the online cosmetics purchasing behavior of students at Ho Chi Minh City University of Industry and Trade. A mixed-methods approach was employed, combining qualitative and quantitative research methods. Qualitative data were gathered through in-depth interviews and focus group discussions, while quantitative data were collected via a structured questionnaire distributed to 212 students with prior experience in online cosmetics shopping. Data analysis was conducted using SPSS 20.0, involving descriptive statistics, Cronbach’s Alpha for reliability testing, exploratory factor analysis (EFA), and correlation-regression analysis. The research identified perceived usefulness, website/app design quality, and return policies as positive influencers of online cosmetics purchasing behavior, while perceived risk negatively impacted it. No significant difference was found between gender and purchasing behavior. The study concludes that students’ online cosmetics purchasing behavior is significantly influenced by perceived benefits and risks, as well as the quality of the shopping platform and policies. These findings provide valuable insights for businesses to optimize their strategies in attracting and retaining student customers. Businesses in the cosmetics industry can leverage these findings to enhance their online platforms, improve customer trust through transparent policies, and tailor marketing strategies to meet the specific needs and preferences of student consumers.